2010
DOI: 10.4061/2010/140539
|View full text |Cite
|
Sign up to set email alerts
|

Alzheimer's Disease: A Pathogenetic Autoimmune Disorder Caused by Herpes Simplex in a Gene-Dependent Manner

Abstract: Herpes simplex is implicated in Alzheimer's disease and viral infection produces Alzheimer's disease like pathology in mice. The virus expresses proteins containing short contiguous amino acid stretches (5–9aa “vatches” = viralmatches) homologous to APOE4, clusterin, PICALM, and complement receptor 1, and to over 100 other gene products relevant to Alzheimer's disease, which are also homologous to proteins expressed by other pathogens implicated in Alzheimer's disease. Such homology, reiterated at the DNA leve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
35
1
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(39 citation statements)
references
References 69 publications
1
35
1
2
Order By: Relevance
“…Similarly, PICALM has been linked also to HSV-1 life cycle, suggesting that PICALM binds to receptors used by HSV-1 for cellular entry, intracellular trafficking, and nuclear egress [128]. On the other hand, it has been suggested that the amino acid stretches (namely vatches) in proteins expressed by HSV-1 are homologous to PICALM and other risk loci and pathogens relevant to AD [129]. Accordingly, immune response triggered by HSV-1 infection may target their human counterparts, leading to protein knockdown and neurons killing [129].…”
Section: Picalm and Immune Disorder In Admentioning
confidence: 96%
“…Similarly, PICALM has been linked also to HSV-1 life cycle, suggesting that PICALM binds to receptors used by HSV-1 for cellular entry, intracellular trafficking, and nuclear egress [128]. On the other hand, it has been suggested that the amino acid stretches (namely vatches) in proteins expressed by HSV-1 are homologous to PICALM and other risk loci and pathogens relevant to AD [129]. Accordingly, immune response triggered by HSV-1 infection may target their human counterparts, leading to protein knockdown and neurons killing [129].…”
Section: Picalm and Immune Disorder In Admentioning
confidence: 96%
“…This aspect still requires further research about what types of pathogens can penetrate the relative immune privilege of the CNS 14 . Some chronic infections caused by prions 15 , bacteria such as Borrelia burgdorferi (Lyme disease) [16][17][18] , or viruses such as Herpes simplex virus 19 can infiltrate the brain and elicit persistent immune reactions. These cases could possibly be treated with antiviral or antibacterial agents if diagnosed early enough.…”
Section: Some Cases Could Be the Results Of Chronic Infectionmentioning
confidence: 99%
“…1,2,3 Rendahnya prevalensi HAD di negara maju tersebut berkaitan dengan meningkatnya penggunaan antiretroviral treatment (ART), namun penurunan angka kejadian HAD tersebut digantikan oleh meningkatnya angka kejadian gangguan kognitif yang lebih ringan terkait 9 Saat ini mulai banyak diteliti mengenai keterkaitan infeksi virus herpes simpleks dengan kejadian penyakit Alzheimer. 12 Prion protein bentuk patogen (PrP Sc ) merupakan penyebab terjadinya Cruetzfeldt-Jacob disease (CJD) yang ditandai dengan demensia progresif. 13 Plasmodium falciparum dan Toxoplasma gondii merupakan protozoa penyebab penting kerusakan jaringan otak.…”
Section: Diskusiunclassified
“…Kondisi yang dapat menyebabkan terjadinya demensia kortikal terkait infeksi diantaranya adalah virus herpes simpleks, prion protein bentuk patogenik (PrP Sc ), Treponema pallidum, dan Borrelia burgdoferi. 12,13,18 Kondisi yang dapat menyebabkan terjadinya demensia subkortikal terkait infeksi adalah meningitis kriptokokal, infeksi HIV-1, prion protein bentuk patogenik (PrP Sc ), dan ensefalitis oleh infeksi CMV. 9,30 Karena demensia terus berkembang, maka defisit yang muncul juga akan semakin berkembang, termasuk diantaranya adalah demensia global.…”
unclassified